Deskripsi Motivasi Belajar Siswa Kelas X SMAN 1 Godean pada Mata Pelajaran Fisika - Helda Noer Ramadhani; Tsania Nur Diyana (Program Studi Pendidikan Fisika, UIN Raden Fatah Palembang, 2024)
The purpose of this study was to describe the learning motivation of class X students of SMAN 1 Godean in physics. This type of research is descriptive research with a quantitative approach. The subjects of this study were students of class X Mipa 3 at SMAN 1 Godean. The research instrument used was a questionnaire on students' motivation to learn physics. This type of research data is quantitative data. The technique used in this research is quantitative analysis using descriptive statistics. The results of this study indicate that the learning motivation of students at SMAN 1 Godean in physics is classified as strong because of the five indicators the percentage above 60% is obtained where the results show a strong category. The results of the study also show that learning motivation is classified as moderate with a percentage of 67%.